DANGER : Life and Death Stories from the US Navy Approach Magazine - Nelson, Derek, 1950-; Parsons, Dave, 1954- (Motorbooks International, 1991)
Danger: life and death stories from the US Navy Approach magazine is an exciting collection of 95 of the best stories from the last 35 years, stories written in adrenaline and fear, shattered canopies, twisted metal and sometimes blood.